The importance of the Autostrain RV technique in the treatment of right ventricular myocardial alterations in patients with breast cancer receiving chemotherapy - Yan Liang; Ping Du; Yabo Song; Xinshi Li; Yingying Han; Hongfang Dongye; Hongqiang Liu; Jinqiu Li (Scientific Reports)
Abstract To research the value of Autostrain right ventricular (RV) technology in detecting and preventing right ventricular myocardial injury in patients undergoing breast cancer chemotherapy by providing an imaging basis for early identification. To examine the changes in various cardiac function parameters before and after chemotherapy, two-dimensional echocardiography was employed 48 h before chemotherapy, 48 h after the fourth cycle of chemotherapy, and 48 h after the eighth cycle of chemotherapy, respectively. The patients included those with breast cancer who underwent surgery and were primarily administered anthracycline-based chemotherapeutic drugs. (1) Compared with the pre-chemotherapy period, the absolute values of the right ventricular global longitudinal strain (RV4CSL) and right ventricular free-wall longitudinal strain (RVFWSL) decreased after the fourth chemotherapy cycle, and no significant differences were observed in tricuspidannular plane systolic excursion (TAPSE), right ventricular Tei index, and right ventricular fractional area change (FAC); (2) Compared with the pre-chemotherapy period, the absolute values of RV4CSL and RVFWSL decreased after the eighth chemotherapy cycle. TAPSE and FAC decreased, the right ventricular Tei index increased; (3) Compared with the end of the fourth chemotherapy cycle, the absolute values of RV4CSL and RVFWSL decreased at the end of the eighth chemotherapy cycle. TAPSE, right ventricular Tei index and FAC were not significantly different. (4) Pearson correlation analysis revealed a correlation between the absolute value of RV4CSL, the absolute value of RVFWSL, right ventricular Tei index, TAPSE and FAC. The absolute values of RV4CSL and RVFWSL are sensitive indices that reflect changes in the right ventricular myocardium in the early stages of chemotherapy. They can reflect the effects of anthracycline on the right ventricular myocardium of patients with breast cancer earlier than the TAPSE, FAC and right ventricular Tei indices. A relationship exists between the absolute value of RVFWSL, the absolute value of RV4CSL, right ventricular Tei index, TAPSE, FAC and anthracycline-induced alterations in the right ventricular myocardium. This study is helpful for early detection of right ventricular myocardial function injury caused by anthracyclines in breast cancer patients, and provides imaging basis for early clinical detection and prevention of right ventricular myocardial injury.